2010
DOI: 10.1017/s0967199410000407
|View full text |Cite
|
Sign up to set email alerts
|

Human zygote morphological indicators of higher rate of arrest at the first cleavage stage

Abstract: A little studied aspect of developmental arrest (DA) in ART is zygote arrest (ZA). Etiologically, blockage at the first cleavage stage includes molecular and chromosomal anomalies, some of which manifest morphologically. Given considerations on embryo culture, transfer and cryopreservation, optimal zygote selection is very important. The aim of this study was to ascertain whether zygote morphological features were indicators of increased ZA. In this study we performed a prospective, observational study of 2105… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 24 publications
2
7
0
1
Order By: Relevance
“…Specifically, our data confirm the efficacy of the pronuclear morphology evaluation to predict the clinical pregnancy [4-11,21]. At this regard, current findings highlight that the pronuclear morphology is an important tool not only to individuate abnormal fertilizations (only 1 PN or more than 2 PN) but to select zygotes when ET is performed at day 1, as recently recommended by the European Society of Human Reproduction and Embryology (ESHRE) [1].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Specifically, our data confirm the efficacy of the pronuclear morphology evaluation to predict the clinical pregnancy [4-11,21]. At this regard, current findings highlight that the pronuclear morphology is an important tool not only to individuate abnormal fertilizations (only 1 PN or more than 2 PN) but to select zygotes when ET is performed at day 1, as recently recommended by the European Society of Human Reproduction and Embryology (ESHRE) [1].…”
Section: Discussionsupporting
confidence: 82%
“…Previous data have suggested that zygote-score could be an efficient tool for embryo selection if combined with embryo morphology evaluation on days 2 and 3 [10,11]. In particular, the morphological characteristics of the human zygote may suggest an increased risk of arrest of the embryo [11]. Moreover, to date, there is not definitive consensus about the clinical efficacy of the zygote pronuclear morphology.…”
Section: Introductionmentioning
confidence: 99%
“…PN and NPB morphologies were previously associated with aneuploidy. [38][39][40][41][42][43] Here we find that the morpho-dynamic properties as characterized by the trajectories of the PN'i and the NPB's differentiate between the potential of MC versus LB outcomes. The maximal distance between NPB pairs within the small PN ( 1 ) is greater in MC embryos than in LB embryos ( Fig.…”
Section: Feature Importancementioning
confidence: 61%
“…In the second one, after the study of 1,894 zygotes, the Authors concluded that zygote score allows to select the most competent embryos to transfer [23]. More recently, Zamora et al [44] confirmed the correlation between NPBs and the cleaved embryos on day 2 in a prospective study conducted on 2,105 zygotes [44]. …”
Section: Resultsmentioning
confidence: 99%